Nation-Level Moderators of the Extent to Which Self-Efficacy and Relationship Harmony Predict Students' Depression and Life Satisfaction: Evidence From 10 Cultures. (July 2016) - Smith, Peter B.; Ahmad, Abd Halim; Owe, Ellinor; Celikkol, Göksu Cagil; Ping, Hu; Gavreliuc, Alin; Chobthamkit, Phatthanakit; Rizwan, Muhammad; Chen, Sylvia Xiaohua; Teh, Hui Bee; Vignoles, Vivian L.
Previous two-nation comparisons have provided evidence that self-efficacy may be a protective factor against depression in individualist cultures, whereas relationship harmony may be a stronger protective factor in collectivist cultures. However, wider sampling and more specific measures of cultural difference are required to test these conclusions. Student ratings of depression and life satisfaction were surveyed in 10 samples drawn from nine nations. Culture-level individualism positively moderated the relationship of self-efficacy to low depression. However, culture-level collectivism negatively moderated the linkage of relationship harmony to depression. To better understand these effects, four separate nation-level predictors derived from dimensions of self-construal were employed. Effects of self-efficacy were strongest where cultural models of selfhood emphasized self-direction (vs. receptiveness to influence); effects of relationship harmony were strongest where cultural models of selfhood emphasized dependence on others (vs. self-reliance). These results illustrate the value of unpackaging the diffusely defined concept of individualism-collectivism.